Effect of Social Skill Training (SST) on Social Interaction in Children With Autism Spectrum Disorder (ASD): Literature Review - Reza Fajar Amalia; Priyo Purnomo As'hab (Ruang Ide, 2022)
Background: Autism is a developmental disorder characterized by impaired language, communication, social interactions, and repeated interactions. Children with autism also have low social awareness and cannot understand or let go of other people's feelings. This causes autistic children to not empathize with others who are essential in social relations, so programmed therapy is needed to train social skills in children with autism spectrum disorder (ASD) through social skills training (SST). Objective: To study the effects of SST therapy on the social interactions of children with autism spectrum disorder (ASD). Methods: The method in this paper is a literature review. Search for research articles using a database of sciences from Science Direct, Scopus, ProQuest, Wiley Online Library, EBSCOhost, Sage Journal, and ClinicalKey. The inclusion criteria for this journal study are human research, discussion in English, free full text, and publications between 2012 and 2019. A total of 10 relevant articles are discussed in this literature review. Results: SST therapy for children with ASD focuses on behavioral and social learning, where children are taught social skills such as making eye contact, starting conversations, and establishing cooperation with others. Conclusion: The application of SST therapy to children with ASD can improve their adaptability to other forms of socialization and social skills and improve their daily lives. Keywords: autism spectrum disorder, social interaction, social skills training,